Domestic cattle breeds in ancient Egypt from the predynastic period through the end of the old kingdom - Bateman, Katherine (AUC Knowledge Fountain, 2018)
From the Predynastic Period through the end of the Old Kingdom phenotypically diverse cattle existed in Egypt. In the literature, cattle from this time period are currently identified by their horns: the longhorn, shorthorn, and hornless. Identifying cattle based on the size of their horns is an inaccurate classification method because horn length and shape varies within a single breed due to factors such as age, sex, and diet, and the words used to describe length (short, medium, and long) are often subjective. This study analyses representations, textual evidence, and physical remains of ancient Egyptian domesticated cattle and attempts to group them into breeds based upon multiple physical characteristics. The goal is to determine the number of cattle breeds (phenotypically expressed) that existed from the Predynastic Period through the end of the Old Kingdom. In this study 'breed' is defined as a group of animals that, as a result of deliberate breeding by humans for selected traits, have certain distinguishable characteristics. The physical characteristics that are analyzed in order to group the cattle into breeds include: horn length and shape, general skull morphology, dewlap size, presence of a cervico-thoracic hump, back shape, tail length, switch shape, and coat color/s. An analysis of the available evidence suggests that there may have been up to six different breeds of cattle during this time period. Some breeds may have been brought from neighboring territories such as Nubia, Libya, and the Near East via trade and/or diplomatic/military missions, while some may have been indigenous to Egypt, the descendants of domesticated wild aurochson. The ancient Egyptians possibly had specialized breeding programs, in which they intentionally crossed different breeds of cattle in order to produce new breeds that were tailored to their needs.